Dual interacting cosmologies and late accelerated expansion - Chimento, Luis Pascual (2006)
In this paper we show that by considering a universe dominated by two interacting components a superaccelerated expansion can be obtained from a decelerated one by applying a dual transformation that leaves the Einstein's field equations invariant. © 2006 The American Physical Society.